PERBEDAAN KADAR HEMOGLOBIN PRATRANSFUSI PADA PASIEN TALASEMIA BETA MAYOR SEBELUM DAN SAAT PANDEMI COVID-19 - Helda Pareang; Harapan Parlindungan Ringoringo; Meitria Syahadatina Noor; Edi Hartoyo; Rahmiati Rahmiati (Homeostasis, 2022)
Beta thalassemia major is a disorder that occurs due to the absence of beta globin chain production and is characterized by severe clinical symptoms. The purpose of this study was to explain the differences in pretransfusion hemoglobin levels in beta thalassemia major patients before and during the COVID-19 pandemic at Idaman Hospital Banjarbaru in 2019-2020. This research was a descriptive-analytic study with a cross sectional approach. Collecting data through medical records of patients with beta thalassemia major. The sampling technique was total sampling. The sample was 35 patients. The results showed that there were 18 women (51,43%) patients, the most age was in the age range 12 - <18 as many as 12 (34,29%) patients, and underweight nutritional status (BB/TB) were 24 (68,57) patients. Pre-transfusion hemoglobin levels were classified into before and during the COVID-19 pandemic. The average value of pretransfusion hemoglobin levels before the COVID-19 pandemic was 8,95 g/dL and during the COVID-19 pandemic was 8,92 g/dL. The test used was the paired sample test and the results obtained were p = 0,83 because p > 0,05, there was no significant difference between pretransfusion hemoglobin levels before and during the COVID-19 pandemic